Pengaruh Penggunaan Media Video Pembelajaran terhadap Hasil Belajar Siswa Kelas IV SD Negeri 097323 Dolok Hataran - Reinha Rosari Simanungkalit; Jumaria Sirait; Emelda Thesalonika (Departement of Mathematics Education, 2023)
The problem in this study is the low IPS scores obtained by students, the lack of learning media used by teachers at SD Negeri 097323 Dolok Hataran. This study aims to find out how the influence of the use of learning video media on social studies learning outcomes for class IV students. The subjects in this study were all of class IV, where the number of students was 30 people consisting of 18 boys and 12 girls. This type of research is quantitative research with a pre-experimental approach. This research started from pre-test to post-test. There were 30 students who did the pre-test and post-test, where the average pre-test score was 64 and the post-test average score was 80. he results of the N-gene test obtained an N-gene score of 0.65 in the moderate or quite effective category. Based on the acquisition of pre-test and post-test data, it can be concluded that learning video media has an effect on student learning outcomes and can improve social studies learning outcomes for class IV students at SD Negeri 097323 Dolok Hataran.